Deformation and partial melting in the Central Zone of the Damara Orogen, Namibia - Goslin, Lechelle Morgan (My University, 2019)
The southern Central Zone of the Damara Belt, Namibia is characterised by northeast-southwest trending basement-cored domes. The Palmenhorst Dome is the largest of these basement-cored domes and the northern extent of this dome forms the focus of this research. Previous studies have shown that these Palaeoproterozoic domes have varied stratigraphies, including infolded Damaran metasediments or they may not be cored by basement lithologies at all. This study aims to re-evaluate the lithologies of the Abbabis Complex in the northern Palmenhorst Dome by means of integrating remote sensing, field mapping, petrographic analysis, whole rock geochemistry and U-Pb-Hf geochronology. Eight major spectral domains were noted in the field area which comprise the Abbabis Complex (domains 1 – 3) within the core surrounded by Damaran metasediments (domains 4 - 8). Several units of the Damara Supergroup were identified in the field area including the Etusis (domain 4), Khan (domains 5 and 6), Rössing (domain 7) and Chuos (domain 8) formations. Anomalous rafts were identified in the basement lithologies and are proposed to be infolded Damaran metasediments or amphibolite dykes. Field work confirmed that these anomalies did in fact represent a combination of these domains. The Abbabis Complex domes yielded compositional heterogeneities and were found to contain textural and compositional variations of granites and orthogneisses, which was confirmed by field mapping, petrographic studies and geochemistry. Detailed zircon U-Pb dating revealed ca. 2 Ga genesis for the Abbabis Complex (1998.6 ± 14.9 Ma, 2002.5 ± 13.9 Ma and 2071.39 ± 5.39 Ma, upper intercept regression ages), confirmed to be of Narubis Granitoid Complex affinity. The succession of metasedimentary units in the field study area is similar to those proposed by previous studies. Lower Damaran units , namely metasediments of the Etusis, Khan, Rössing and Chuos formations, were identified in D2 synclines infolded into the basement-cored domes. The synclines identified in this study include the Ostrich Gorge, Hinge and Dorob synclines. The Etusis Formation yielded detrital age peaks of 1 and 2 Ga, which are correlatable to sedimentary rocks analysed in other studies along the southern Congo Craton edge. Unradiogenic εHf values indicate that the Etusis Formation had three main provenance sources and a minor Abbabis Complex affinity. The three main source regions include a younger 1 Ga source that was formed from recycled (εHf = -25 to -28) Archaean (3.3 – 3.6 Ga) sources (Et1), another 1 Ga source that was crustally derived (and recycled; εHf= -11 to -17) from Archaean (2.6 - 2.9 Ga) sources (Et2), a juvenile source (εHf= + 4 to +9) that was extracted from the Depleted Mantle and crystallised new Eburnean crust (2.2 - 2.4 Ga) (Et3). These sources can be attributed to the Congo Craton. Zircon Hf isotope systematics (εHf of 2.8 o -8.8 with DM model ages of 3.1 to 2.8 Ga) suggest a Congo Craton affinity for the Abbabis Complex. The Damaran granitoids (red granites, grey granites and sheeted leucogranites) are comparable to those found by other workers and the amphibolite dykes were found to be Damaran in age (550.48 ± 0.85 Ma, zircon concordia age) and are associated with the Goas Intrusive Suite. The syn-tectonic red (535.77 ± 0.96 Ma, zircon concordia age) and grey granites were emplaced shortly after the amphibolite dykes during early phases of collision and are typically associated with M1 metamorphism. The sheeted leucogranites were variably emplaced as post-tectonic granites during orogenic collapse (D2 and D3). These Damaran granitoids were found to be a result of biotite-dehydration melting and exhibited various modes of crystallisation from cumulates (enriched REE, positive Eu anomaly) to fractional crystallisation as final melts (REE enrichment, negative Eu anomaly). All these granitoids and the amphibolites show unradiogenic εHf values, which indicate crustal reworking of variably aged Archaean- to Mesoproterozoic-aged crust during the Pan-African orogeny. Detailed structural and lithological mapping revealed pre-Damaran and Damaran deformational histories. However, except for a pre-Damaran fabric, the pre-Damaran deformation is not always identifiable. The Damaran deformation is divided into four main events (D1 to D4). The main features associated with each event include (D1) a regional fabric with intrafolial folds (560 – 540 Ma), (D2) recumbent southwest verging folds, associated limb parallel high strain zones (525 – 510 Ma) from orogenic collapse, (D3) upright and open interference folds which lead to dome formation and (D4) brittle deformation associated with conjugate sets of faults/joints. These main events correlate to the main phases of the Damara Orogen from Khomas Ocean closure to Congo-Kalahari collision. An early metamorphic event (M1) is associated with the emplacement of the red granites and D1, with U-Pb concordia ages established from multiple metamorphic zircons (560 – 540 Ma). The second, and most prominent metamorphic event (M2) outlived D2 deformation and resulted in post-tectonic leucogranites. This event was constrained by the U-Pb concordia ages for type C’ sheeted leucogranites of 525.72 ± 1.91 Ma and regressed metamorphic zircons from various granites (525 – 510 Ma).
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fullfillment of the requirements for the degree of Master of Science, Johannesburg, 2019